MICROSOFT VISUAL BASIC 6.0 APPLICATION FOR CASH TRANSACTIONS IN STORES GANI - Lidia Adisti Gunara; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2003)
In stores this system is required for Gani to improve services with this system cangenerate good sales report daily or monthly. In making this system assisted with theprogramming language Microsoft Visual Basic 6.0. The database is also built withthis software by using visdata.